Spatial Approach to Infiltration and Groundwater Level: Implications For Sustainable Settlement Planning - Widodo, Trisno; Antariksa, Antariksa; Putra, Fadillah; Hariyani, Septiana (Postgraduate School of Universitas Brawijaya, 2025)
Rapid land use change due to population growth and urbanization presents significant challenges to urban development. This study aims to map the groundwater level and water infiltration conditions in residential areas and investigate the conditions in the Kanigoro Urban Area. This research identifies a spatial approach to analyze satellite image maps with ARC GIS software for land cover changes that overlap with slope maps, soil types, rainfall, groundwater basins, groundwater flow patterns, and spatial pattern plan maps to obtain water infiltration conditions and building distribution. The analysis showed that water infiltration capacity has been reduced due to converting open land into built-up areas, resulting in decreased groundwater quality and quantity and an increased risk of flooding. Based on water infiltration capacity and potential environmental impacts, this map recommends the best locations for settlement development. The results show that the water infiltration condition of most settlement areas in the Kanigoro Urban Area is critical or rather critical. Therefore, efforts must be made to increase water infiltration capacity by implementing sustainable drainage systems, developing green open spaces, and utilizing environmentally friendly technologies. This research produced a settlement direction map based on the analysis of water catchment conditions and groundwater levels that can be used by local governments when they make better and more sustainable spatial plans. Keywords: infiltration, spatial approach, sustainable settlement